The Effect Of Bank Health Level On Profitability Using The RGEC Method: Comparative Study On BCA Banks and BCA Syariah Banks - Milza, Anita Tri; Bahrudin, Moh.; Rosilawati, Weny; Faizah, Iva (Al-Mashrof: Islamic Banking and Finance, 2023)
This study used a comparative quantitative approach with purposive sampling as the sampling technique. The sample used is the quarterly financial performance for 2017-2021 with a total of 20 samples. Data is obtained secondary through quarterly reports published on the website of each bank in 2017-2021. Data analysis in this study used the help of eviews 10.The results of this study revealed that at Bank BCA all variables were at a very healthy composite-1 (PK-1) rating. For Bank BCA Syariah, only the NPF and CAR components in composite-1 (PK-1), partially there are significant differences in the two banks related to the variables that affect their profitability, namely NPL and BOPO at Bank BCA while for Bank BCA Syariah, namely BOPO and CAR, simultaneously there is no difference, where all level variables together have a significant effect on profitability, namely at Bank BCA (Sig 0.00 < 0.05) and Bank BCA Syariah (Sig 0.00 < 0.05) so that with a high RGEC value it will give good results healthy on the profitability of a bank. Keywords: NPL/NPF, GCG, BOPO, CAR, ROA